Formulasi Ilam dalam Konteks Tabligh - Aliyudin, Mukhlis (Prophetica, 2009)
Since the information era that leads by technological growth, tabligh has been enhanced in forms and areas. Among areas and domain of tabligh activities is !lam (broadcasting). Nevertheless, seeking the formula of !lam is not that simple therefore it need some serious efforts so can be appiicable in practives. On the other hand, Ilam needs some effort that more than justification of Islam on the growth of technological and information phenomena